PENYALURAN ZAKAT PERUSAHAAN PADA BANK UMUM SYARI’AH DI ACEH DAN RELEVANSINYA DENGAN QANUN NO. 3 TAHUN 2021 - Nadia Ulfa Sh; Ridwan Nurdin; Yuhasnibar (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2022)
The aim of this research is to find out the concept and mechanism for distributing corporate zakat to Sharia Commercial Banks, and to find out what the challenges and obstacles are in disbursing corporate zakat at Sharia Commercial Banks in Aceh. This study uses a normative sociological approach and a qualitative type of research using secondary data in the form of BUS annual reports for the period 2020 to 2021. The sample selection that researchers used in this research were 4 samples from Sharia Commercial Banks which published complete financial reports during the 2020-2021 period. Data collection techniques through interviews and documentation data. The research results obtained show that of the 4 Sharia Commercial Banks, only Bank Muamalat Indonesia pays company zakat and the other 3 banks only pay employee zakat. However, in 2020 these three banks did not pay zakat to Baitul Mal. One of the obstacles or causes of some Sharia Commercial Banks not issuing zakat to Baitul Mal was that at that time Covid-19 was rife, this resulted/had the impact of these banks experiencing a decrease in income or it could be said that their economy was paralyzed due to the impact of Covid-19. In the end, the zakat management organization's income fell. So the zakat that should have been issued by the company to Baitul Mal has been distributed to the handling of the coronavirus public health center for needs during the pandemic, the aim is so that the community can avoid the Covid outbreak that is currently hitting.